El primer año de los profesorados en lenguas extranjeras en Argentina: discursos sobre la inclusión y errores del estudiantado (Investigaciones) - Camargo Angelucci, Thalita (2024)
The error-correction dynamic works as a centripetal force in the debates on teaching in the field of education and, particularly, language education. In this context, this work is based on a research project that analyzed the discourse of Argentine teacher trainers of English, Portuguese, and French about the way they deal with their students’ errors. To do so, fifteen teachers of the three aforementioned languages were interviewed based on a thematic script. The interviews were transcribed and discursively analyzed around different categories. The aim of this paper is to specifically analyze the relationship between the treatment of errors in the first year of foreign language teacher training and inclusive education. In the analyses, we noticed the incidence of interdiscourses related to the socalled governmental ‘inclusive policies’ that coincide with the sanction of Law No. 27204 in 2015. The results show the didactic challenges of first-year teachers who face a heterogeneous student body. The conclusion states that this problem exacerbates the academic situation of the most vulnerable students who starts higher education in conditions of socioeconomic and cultural disadvantage, while knowledge of foreign languages persists as cultural capital of privileged social classes.